2013
DOI: 10.1177/0960327113506240
|View full text |Cite
|
Sign up to set email alerts
|

The effect of melatonin on acetylsalicylic acid-induced kidney and testis damage

Abstract: The aim of this study was to evaluate the acute effect of high-dose acetylsalicylic acid (ASA) on kidney and testis, and the potential protective and therapeutic effects of melatonin on ASA-related pathology. A total of 40 rats were randomly divided into the following 5 groups ( n = 8): group 1: control, not given any drug; group 2: only 200 mg/kg ASA was given; group 3: 5 mg/kg melatonin was given 45 min before administering 200 mg/kg ASA; group 4: 5 mg/kg melatonin was given 45 min after administeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Our observations are consistent with earlier studies of melatonin effects on antioxidants [33][34][35][36][37]. We investigated earlier the protective and therapeutic effects of melatonin treatment against ASA induced kidney and testis damage [38]. We found that ASA increased MDA levels in both kidney and testis significantly, whereas it decreased the levels of SOD, CAT, GPx and GSH significantly in the kidney and CAT levels in testis.…”
Section: Discussionsupporting
confidence: 91%
“…Our observations are consistent with earlier studies of melatonin effects on antioxidants [33][34][35][36][37]. We investigated earlier the protective and therapeutic effects of melatonin treatment against ASA induced kidney and testis damage [38]. We found that ASA increased MDA levels in both kidney and testis significantly, whereas it decreased the levels of SOD, CAT, GPx and GSH significantly in the kidney and CAT levels in testis.…”
Section: Discussionsupporting
confidence: 91%
“…The dead cells, which release ROS, and pro-and anti-inflammatory cytokines, and endothelial and macrophage-like cells activated by ionic reactions, can lead to this inflammatory response that can last a long time and causes irreversible tissue damage. 47 Our study demonstrated that ISO was a powerful oxidizing agent that caused a significant oxidative damage in the rat heart tissue. Additionally, our study showed that DEX could potentially be used as a treatment to prevent oxidative damage by ISO.…”
Section: Discussionmentioning
confidence: 57%
“…More recently, we highlighted that oxidative stress, due to the overproduction of ROS and a decrease in the antioxidant level, causes membrane lipid peroxidation, oxidation of cell proteins, damage within the DNA helix and cell death, and also initiates an inflammatory response cascade. The dead cells, which release ROS, and pro‐ and anti‐inflammatory cytokines, and endothelial and macrophage‐like cells activated by ionic reactions, can lead to this inflammatory response that can last a long time and causes irreversible tissue damage . Our study demonstrated that ISO was a powerful oxidizing agent that caused a significant oxidative damage in the rat heart tissue.…”
Section: Discussionmentioning
confidence: 60%
“…The administration of melatonin reduced both adverse conditions [15]. This protective effect of melatonin has been reported against oxidative damage induced by aluminum in rats’ kidneies [16], acetylsalicylic acid-induced kidney and testis damage [17], decreased urinary excretion of n-acetyl-bd-glucosaminidase, and albumin and renal oxidative markers in diabetic rats [18].…”
Section: Introductionmentioning
confidence: 93%